Locations, Outcomes, and Selective Migration - Vigdor, Jacob L. (The Review of Economics and Statistics, 2002)
Studies attempting to link locational attributes and individual outcomes often focus on children or young adults, under the presumption that their location was exogenously determined by their parents. This strategy is more difficult to justify if parents migrate selectively and tend to transmit their own characteristics to their children. This paper uses Census microdata to document a strong link between selective migration in one generation and economic outcomes in the next. I show that selective migration is a possible explanation for a puzzle in the existing literature: the changing relationship between segregation levels and individual outcomes within the black population.